Effects of online college student's Internet self-efficacy on learning motivation and performance - Chang, Chiung-Sui; Liu, Eric Zhi-Feng; Sung, Hung-Yen; Lin, Chun-Hung; Chen, Nian-Shing; Cheng, Shan-Shan (Innovations in education and teaching international, 2014)
This study investigates how Internet self-efficacy helps students to transform motivation into learning action, and its influence on learning performance. In this study, the effects of Internet self-efficacy on motivation and the learning performance of online college students were examined using social cognitive theory. The subjects of this study were 87 college students participating in an online course. We applied quantitative analysis to elucidate the relationship between student-perceived Internet self-efficacy and learning performance. The effects of Internet self-efficacy on student motivation and learning performance were evaluated through the analysis of variance. Students with high Internet self-efficacy outperformed those with low Internet self-efficacy on the final exam and were more confident in their ability to complete an online course. Significant gender differences were noted, in which males had a higher degree of Internet self-efficacy and confidence than females; whereas, females had higher scores of online discussion participation and the final exam than males. Regarding the learning motivation, the influence of Internet self-efficacy of males on the dimensions of relevance and confidence in the attention, relevance, confidence, satisfaction motivation model were stronger than females. Therefore, educators are encouraged to identify the psychological characteristics of online learners to provide suitable support for their learning.